Assessing antimicrobial use patterns in Christian Health Association of Malawi (CHAM) health facilities: A cross-sectional study protocol. - Evans Chimayi Chirambo; Francis Kachidza Chiumia; Dumisani Nkhoma; Collins Mitambo; Sharon Odeo; Patience Khomani; Innocent Chibwe; Simon Matchado; Pacharo Matchere; Beatrice Chiweza; Elled Mwenyekonde; Elizabeth Kampira; et al. (PLoS ONE)
The threat of antimicrobial resistance (AMR) in Malawi is high with reported mortality of 19,300 annually, the 23rd highest age-standardised mortality. One of the drivers of AMR is misuse of antibiotics, a phenomenon that has not been adequately researched in Malawi. This study aims to investigate antimicrobial use using health facility, prescribing and patient indicators in Christian Health Association of Malawi (CHAM) health facilities. This will be a multiple cross-sectional study, which will collect data from facilities (22), prescriptions (660), and patients (303). Data will be collected using KoboToolbox v2021, and exported into Microsoft Excel version 2016 for cleaning and coding. Variables will be categorised according to the antimicrobial use indicators. The study will use STATA Version 14 statistical software for data analysis. Subsequently, facilities will be entered into ArcGIS Version 10.7.1 to map hotspots of irrational antimicrobial use. The study will run from October 2024 to June 2025. This study will provide detailed information on frequently used antimicrobials, the cost of antimicrobials relative to medicine budget, the intensity of exposure to antimicrobials, the availability of antimicrobials, patients' understanding of antimicrobials use, and availability of important documents for antimicrobial use. Secondarily, the study will unravel the prevalence of irrational antimicrobial use, the main factors contributing to it, and location where irrational use is most prevalent. These findings will inform the national antimicrobial stewardship action plan, aiming to safeguard the available antimicrobials.